1979
DOI: 10.1128/mmbr.43.2.117-144.1979
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of cell walls of fungi.

Abstract: FORMATION OF CELL WALLS .120 General .120 Biosynthesis of Individual Wall Components .121 Chitin .121 Glucans .124 ten on this subject in the last years (e.g., 5, 9, 10, 15, 16, 205). However, some general explanations are necessary to serve as an introduction to the problem of fungal cell walls. Chemical Structure The remarkable properties of fungal walls, such as their mechanical strength, morphological features, and biological activity, are undoubtedly based on their particular chemical composition. Bartnic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1
5

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(65 citation statements)
references
References 168 publications
(268 reference statements)
2
57
1
5
Order By: Relevance
“…In the present study, we demonstrated that W(}.4-binding sites are indeed associated with oligomers or polymers of chitin since the control experiments successfully abolished the labelling only when the lectin was incubated with N. N', Af"-triacetylchitotriose (a short oligomer of chitin). This observation is in agreement with the general observation that chitin is present in cell walls of the majority of filamentous fungi (Bartnicki-Garcia, 1968;Farkas, 1979).…”
Section: S C U S S I O Nsupporting
confidence: 92%
“…In the present study, we demonstrated that W(}.4-binding sites are indeed associated with oligomers or polymers of chitin since the control experiments successfully abolished the labelling only when the lectin was incubated with N. N', Af"-triacetylchitotriose (a short oligomer of chitin). This observation is in agreement with the general observation that chitin is present in cell walls of the majority of filamentous fungi (Bartnicki-Garcia, 1968;Farkas, 1979).…”
Section: S C U S S I O Nsupporting
confidence: 92%
“…Chitin and chitosan are biosynthetically related and are essential wall components of a wide variety of yeasts and fungi. Both are derived from UDP-GlcNAc (Bartnicki-Garcia, 1968;Farkas, 1979). In S. cerevisiae, chitin fulfils an essential role in cell proliferation, as it is needed in wild-type cells to form the chitin ring, the primary septum and eventually the bud scar remaining on the mother cell after cytokinesis (Cabib et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…6-methoxymellein has previously been considered as an effective phytoalexin (Davies & Lewis, 1981;Goodliffe & Heale, 1978) (Coté & Hahn, 1994). The β-1,3-glucanases show their inhibitory efficacy against plant pathogens by hydrolysing β-1,3-glucans available in fungal cell walls (Farkas, 1979) which can induce resistance by biological and chemical elicitors (Aleandri, Reda, Tagliavento, Magro, & Chilosi, 2010;El-Borollosy & Oraby, 2012;Li, Xu, Zhang, & Cai, 2004). The peroxidases increase the resistance of plants against phytopathogens through reinforcement of cell wall done by catalysing lignification, and creation of toxic surroundings for the pathogen (Passardi, Cosio, Penel, & Dunand, 2005).…”
Section: Discussionmentioning
confidence: 99%